2014
DOI: 10.1590/s0100-06832014000200031
|View full text |Cite
|
Sign up to set email alerts
|

Resistência tênsil de agregados e compressibilidade de um solo construído com plantas de cobertura em área de mineração de carvão em Candiota, RS

Abstract: A recuperação de áreas degradadas após a mineração de carvão é fundamental para a sustentabilidade do meio ambiente. Este trabalho objetivou avaliar a qualidade estrutural de um solo construído sob diferentes plantas de cobertura, utilizando como referência um solo construído sem plantas de cobertura e um solo natural sob vegetação nativa à frente da mineração. Concluiu-se que as plantas de cobertura, principalmente a Tanzânia (Panicum maximum), contribuíram para melhoria da qualidade estrutural do solo constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 32 publications
4
11
1
7
Order By: Relevance
“…The reduction either of TOC content, or of the physical fractions, increases the TS values. These results corroborate Tormena et al (2008b), Ferreira et al (2011), and Reis et al (2014b), who reported the increased TOC contents reduced the TS values, even in clayey soils.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The reduction either of TOC content, or of the physical fractions, increases the TS values. These results corroborate Tormena et al (2008b), Ferreira et al (2011), and Reis et al (2014b), who reported the increased TOC contents reduced the TS values, even in clayey soils.…”
Section: Resultssupporting
confidence: 89%
“…In addition, studies on the soil structural quality, associated with different soil managements, have been postulated for soil tensile strength (TS) and friability (F) (Blanco-Moure et al, 2012;Reis et al, 2014aReis et al, , 2014b.…”
Section: Introductionmentioning
confidence: 99%
“…The species analyzed in this study were Urochloa humidicola, Panicum maximum, and Urochloa brizantha. In order to evaluate the changes resulting from the soil construction and the approximate time of recovery of soil properties, a natural soil under native vegetation was used as reference, located near the excavated strip at the time (in 2010), whose properties were determined in a previous study by Reis et al (2014). …”
Section: Study Areamentioning
confidence: 99%
“…Coal is an important component of the energy matrix in the world and in Brazil; however, the process of open-pit mining damages the environment, although these areas are recoverable (Reis et al, 2014). In Brazil, the state of Rio Grande do Sul accounts for 89.25% of coal reserves, followed by Santa Catarina, with 10.41%; Paraná, with 0.32%; and São Paulo, with 0.02%.…”
Section: Introductionmentioning
confidence: 99%
“…The waste from mining is commonly composed of sub-surface soil horizons that were removed from the pit and rock formations (argillites or siltites), which overlap coal layers (Reis et al, 2014).…”
Section: Introductionmentioning
confidence: 99%